2018
DOI: 10.1101/265272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence in form and function overcomes non-parallel evolutionary histories in a Holarctic fish

Abstract: AbstractUnderstanding the extent to which evolution is predictable under multifarious selection is a longstanding question in evolutionary biology. However, the interplay of stochastic and contingent factors influencing the extent of parallelism in nature is not well understood. To test the predictability of evolution, we studied a ‘natural experiment’ on different organismal levels across lakes and evolutionary lineages of a freshwater salmonid fish, Arctic charr Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 88 publications
(136 reference statements)
3
21
0
Order By: Relevance
“…These results suggest a repression of expression of genes related to growth and developmental process in the limnetic species while genes associated with a higher metabolism and shorter cell cycle life are overexpressed in the limnetic species relatively to the benthic species. These observations at the epigenetic level corroborate those of previous studies at the transcriptomic and physiological levels performed on these populations and further supports the hypothesis of life history trade-offs between survival (limnetic) and growth (benthic) functions revealed in our previous transcriptomic studies [8,48,[66][67][68]. On the other hand, none of the convergent DMRs belong to a DEG, suggesting that methylation differentiation is not a major mechanism involved in the highest differential of gene expression associated to the divergence of limnetic and benthic species.…”
Section: Functional Effect Of Convergent Dmrssupporting
confidence: 90%
“…These results suggest a repression of expression of genes related to growth and developmental process in the limnetic species while genes associated with a higher metabolism and shorter cell cycle life are overexpressed in the limnetic species relatively to the benthic species. These observations at the epigenetic level corroborate those of previous studies at the transcriptomic and physiological levels performed on these populations and further supports the hypothesis of life history trade-offs between survival (limnetic) and growth (benthic) functions revealed in our previous transcriptomic studies [8,48,[66][67][68]. On the other hand, none of the convergent DMRs belong to a DEG, suggesting that methylation differentiation is not a major mechanism involved in the highest differential of gene expression associated to the divergence of limnetic and benthic species.…”
Section: Functional Effect Of Convergent Dmrssupporting
confidence: 90%
“…Consistent with results from the negative binomial glm, the RDA allowed identifying a parallel genetic basis of phenotypic and ecological divergence by revealing parallel DEGs between limnetic and benthic species. Moreover, we found that these DEGs are involved in several metabolic pathways belonging to energetic, growth, cell cycle metabolisms and transcription factor, regulating genes associated with energetic metabolism, as observed in Jacobs et al (). This approach also allowed detecting congruent expression signals at the integrated pathway scale, where the same effect on the selected phenotype can be achieved via regulation of different genes, because of the complexity and redundancy of the multigenic regulatory systems (Yeaman, ).…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with results from the negative binomial glm, the RDA allowed identifying a parallel genetic basis of phenotypic and ecological divergence by revealing parallel DEGs between limnetic and benthic species. Moreover, we found that these DEGs are involved in several metabolic pathways belonging to energetic, growth, cell cycle metabolisms and transcription factor, regulating genes associated with energetic metabolism, as observed in Jacobs et al (2018).…”
Section: Discussionmentioning
confidence: 64%
“…The morphs in Loch Stack (Adams et al 2008) and Loch Tay (Garduño-Paz et al 2012) are clearly of allopatric origin. A recent genome-wide study of sympatric charr in Scotland and Siberia is consistent with sympatric origins of charr morphs (Jacobs et al 2018). Ecological specialization can lead to differential growth, behavior and maturity that may influence both choice of spawning sites and timing of spawning.…”
Section: Genetic Separation Of Recently Evolved Sympatric Morphsmentioning
confidence: 63%
“…Analyses of other scenarios, i.e. with changing migration rates or introgression would be most interesting (see for example Jacobs et al 2018). Considering the episodic nature of ice retreat and the high geological activity in the Þingvallavatn area during the formation of the lake (Saemundsson 1992;Norðdahl et al 2008) charr may have invaded the waters more than once, or experienced intromittent isolation of populations in rifts.…”
Section: Genetic Separation Of Recently Evolved Sympatric Morphsmentioning
confidence: 99%